Work Climate and Turnover Intention Among Nurses in Tertiary Level Hospitals, Republic of The Gambia. - Jaw , Fanta Secka; Akkadechanunt , Thitinut; Wichaikhum , Orn-Anong (Nursing Journal CMU, 2020)
Work climate is a significant predictor of nurse turnover, which can be evaluated by turnover intention. The purposes of this study were to examine levels of work climate and turnover intention, and to explore the relationship between them among nurses in six tertiary level hospitals in the Republic of The Gambia. Participants included 201 nurses who were randomly selected from different departments of these six tertiary level hospitals. Research instruments used in this study were the demographic data form, CRISO Psychological Climate Questionnaire (CRISO-PCQ), and Turnover Intention Scale (TIS). The validity of the CRISO-PCQ and TIS were confirmed by the developer. The reliability of the CRISO-PCQ was 0.92, and TIS was 0.80. Data were analyzed using descriptive statistics and Pearson product moment correlation. The results of the study are as follows: The level of overall work climate as perceived by nurses was positive. Among the 15 dimensions of work climate, 9 were positive and 6 were negative. The overall level of turnover intention as perceived by the nurses was at a high level. There were significant negative relationships between the overall and 13 dimensions of work climate and overall turnover intention. However, two dimensions of work climate were not related to overall turnover intention. The results of this study could be used by nursing administrators in the Republic of The Gambia to develop strategies for improving a negative work climate in order to minimize turnover intention in the six tertiary level hospitals included in this study.